Pengembangan Model Antropometri dan Fungsinya Atlet Selam Kabupaten Pasuruan - Renaldo Sudikdo; Achmad Widodo; Awang Firmasyah; Joesoef Roepajadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was carried out with the primary objective of developing a standardized anthropometric testing model to significantly improve the performance of divers in Pasuruan Regency. This developed model serves as an essential predictive and evaluative tool in the context of athlete training and selection. The study employed a descriptive quantitative method, involving a total of 17 active divers, comprising 10 male athletes and 7 female athletes. Data collection was conducted through a series of basic anthropometric measurements relevant to diving sports, including body height, body weight, arm span, and leg length. Comprehensive statistical analysis revealed a significant and positive relationship between the various measured anthropometric variables and key diver performance parameters. The main findings of the research clearly indicate that the developed anthropometric testing model has a strong and significant correlation with the enhancement of the divers' strength, speed, and endurance. In other words, this model is capable of providing accurate insights into the potential and actual performance status of the divers. The practical implications of this study are highly significant, as it enriches knowledge and technological innovation in the field of diving sports training. Furthermore, the model offers concrete support for coaches in more objective athlete selection, the design of more personalized and structured training programs, and indirectly contributes to the improvement of a diver's quality and self-confidence. Therefore, this anthropometric testing model is recommended for widespread use as a strategic tool in all stages of selection, training, and long-term development of diving athletes.